Transferrin receptor-mediated internalization and intracellular fate of conjugates of a DNA aptamer - Nan Zhang; Junyan Wang; Tao Bing; Xiangjun Liu; Dihua Shangguan (Elsevier, 2022)
Aptamers have excellent specificity and affinity in targeting cell surface receptors, showing great potential in targeted delivery of drugs, siRNA, mRNA, and various nanomaterials with therapeutic function. A better insight of the receptor-mediated internalization process of aptameric conjugates could facilitate the design of new targeted drugs. In this paper, human transferrin receptor-targeted DNA aptamer (termed HG1-9)-fluorophore conjugates were synthesized to visualize the internalization, intracellular transport, and nano-environmental pH of aptameric conjugates. Unlike transferrin that showed high recycling rate and short duration time in cells, the synthetic aptameric conjugates continuously accumulated within cells at a relatively slower rate, besides recycling back to cell surface. After long incubation (≥2 h), only very small amounts of HG1-9 conjugates (approximately 5%) entered late endosomes or lysosomes, and more than 90% of internalized HG1-9 was retained in cellular vesicles (pH 6.0-6.8), escaping from degradation. And among the internalized HG1-9 conjugates, approximately 20% was dissociated from transferrin receptor. The lower recycling ratios of HG1-9 conjugates and their dissociation from receptors promote the accurate and efficient release of their loaded drugs. These results suggest that aptamer HG1-9 could be provided as a versatile tool for specific and effective delivery of diverse therapeutic payloads.